Guideline on radiation protection in medicine requires documentation of radioiodine therapy and follow-up - Koch, W.; Rosa, F.; Knesewitsch, P.; Hahn, K. (Nuklearmedizin - NuclearMedicine, 2005)
Aim: The lately updated German guideline on radiation protection in medicine (Richtlinie Strahlenschutz in der Medizin) requires the physician who administers radioactive substances for therapy, to perform and document follow-ups. In order to decrease the administrative burden, an electronic database was developed that interfaces with a word processing software to generate written reports and statistic analysis. Methods: Based on Microsoft® Access and Microsoft® Visual Basic a database was created to monitor patients with benign and malignant thyroid disorders after radioiodine therapy. It permits automatic creation of therapy documents and necessary patient reports in Microsoft® Word. Intuitive handling, third level of normalization in database architecture and automatic plausibility checks guarantee integrity of the data and the efficacy of the database. Results, conclusion: The new software has been a success in over 1500 patients and over 3800 in- and outpatient therapies and visits. The effort of data entry is easily offset by the automatic generation of the necessary patient reports. The required supervision of the follow-up appointments is now also user-friendly and efficient.
Keywords: Thyroid carcinoma; radioiodine therapy; monitoring; follow-up